Method of evaluation of the extent of skeletal forms of malocclusion - I. N. Zhmyrko; N. S. Drobysheva (LLC "Endo Press", 2020)
An integrated approach to diagnostics for choosing a treatment strategy helps to obtain stable, functionally complete results and minimizes the relapse possibility. In skeletal forms of distal malocclusion, it is necessary to take into account the severity of maxillofacial changes to choose a treatment algorithm.For this aim, to assess the severity of dentofacial anomalies an index has been developed.Materiais and methods. To develop the index 60 patients with varying degrees of distal occlusion were examined comprehensively. Dental casts, photometry and a lateral cephalography were analyzed.Resuits. Aftera statistical analysis of the data, an index that reliably proves the severity of maxillofacial anomalies was created, which is rationale for choosing a method of treating patients with skeletal form of distal occlusion: orthognathic or compensatory orthodontic treatment.Conciusions. The proposed technique is a convenient express method for the diagnosis and treatment planning in patients with dento-maxillofacialanomalies.